2019
DOI: 10.3390/rs11030299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Urban Redevelopment on Surface Urban Heat Islands

Abstract: Climate change is a global challenge with multiple consequences. One of its impacts is the increase in heatwave frequency and intensity. The risk is higher for populations living in urban areas, where the highest temperatures are generally identified, due to the urban heat island effect. This phenomenon has recently been taken into account by local elected officials. As a result, developers have decided to use solutions in redevelopment projects to combat high temperatures in urban areas. Consequently, the obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 92 publications
(128 reference statements)
2
51
0
6
Order By: Relevance
“…In future studies, other factors, for example, high-resolution building height, albedo, and sky views related to urban LST could be investigated in the downscaling process. The results can potentially contribute to improving our understanding of heat exchange processes in urban environments and has wide contributions in meteorological, hydrological, and ecological research [52].…”
Section: Discussionmentioning
confidence: 95%
“…In future studies, other factors, for example, high-resolution building height, albedo, and sky views related to urban LST could be investigated in the downscaling process. The results can potentially contribute to improving our understanding of heat exchange processes in urban environments and has wide contributions in meteorological, hydrological, and ecological research [52].…”
Section: Discussionmentioning
confidence: 95%
“…Semi-Empirical Methods (SEMs), Physically-Based Methods (PBMs), and multi-channel Temperature/Emissivity Separation (TES) methods are three distinctive categories for LSE retrieval from space [7]. PBMs and multi-channel TES methods are not operational for Landsat data to obtain LSE due to the limitations presented in many studies, such as the requirement of more than two TIR bands or nighttime images [7,46,[76][77][78][79]. SEMs contain the Classification Based Emissivity Method (CBEM) [74,80] and the NDVI Based Emissivity Method (NBEM) [81,82], which are suitable for LSE estimation from Landsat data.…”
Section: Land Surface Emissivity (Lse) Modelsmentioning
confidence: 99%
“…GIS-based methodology to evaluate green roofs and green urban areas 9 [4][5][6][7][8][9][10][11][12] Outdoor thermal comfort: UHI mitigation strategies and thermal comfort indexes 20 [2,4,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Energy savings and Indoor thermal comfort from Green roofs 5 [1,[31][32][33][34] 2.…”
Section: No Of Papers Sourcementioning
confidence: 99%
“…Various studies have been conducted to investigate UHI, using, for example, satellite images, surveys, building footprints and morphological parameters [13,23]. Renard et al [22] examined UHI by analysing satellite images, and the study showed that heavy renovations are necessary to achieve a decrease in surface temperature and that the results are related to the increase in green urban spaces. A similar approach [13] confirmed that, by increasing the green roofs and changing the albedo of roofs, surface temperatures reduce linearly.…”
Section: Outdoor Thermal Comfort: Uhi Mitigation Strategies and Thermmentioning
confidence: 99%
See 1 more Smart Citation